Pain expression and intercultural identity: a comparison between English and Persian among EFL learners - Hakimeh Abedini (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract The study of pain expression and its cultural nuances has received considerable attention in the past decades. However, the scope of research on the connection between pain and intercultural identity has received little attention. In this context, the present study examined how Iranian EFL learners articulate pain in English and Persian, elucidating the intricate dynamics of linguistic expression and intercultural identity formation. Data were collected from structured expression prompts, open-ended questions, and metaphor completion tasks in which 20 Iranian EFL learners were asked to describe their experiences of pain in both English and Persian. The qualitative data analysis indicated that expressions of pain among participants are deeply rooted in their intercultural identities and manifest through distinct linguistic strategies in both languages. Persian was often used for its emotionally resonant and metaphor-rich expressions, reflecting the cultural and historical depth of the language. In contrast, English was preferred for its precision, brevity, and suitability for maintaining privacy. While some participants faced challenges articulating pain in English, others reported feeling more comfortable and less shy due to their exposure to English-speaking contexts. Instances of code-switching further highlighted the dynamic negotiation of identity and emotional expression across languages. These findings have significant implications for healthcare, education, and social integration. In healthcare, understanding cultural variations in pain expression can improve patient–provider communication and foster more empathetic care. In education, integrating cultural context into language instruction can enhance learners’ ability to convey complex emotions authentically. Finally, in social integration, respecting diverse emotional expressions can promote inclusivity and strengthen the sense of belonging among migrant communities.